Young Prostitutes. An Analysis of Social Degradation in 100 Cases (Archives of Criminology, 1964)
This contribution provides an analysis of one of the forms of the social degradation of girls viz. prostitution, on the basis of an investigation which has comprized one hundred girls and young women, below twenty-five years of age, all of them living in Warsaw. The way in which the materials have been collected authorizes one to suppose that the latter is representative, in the sense that many features typical for the girls under investigation will also prove to be such with regard to other juvenile prostitutes in the milieu of a great city. The prostitutes below twenty-five years of age constitute about forty per cent, of the total number of the women who practice prostitution, and who are known as such to the police. Even though, under the new social and economic conditions, the dimensions of prostitution in Poland are now incomparably smaller than they used to be in the pre-war period, yet the existence of that troublesome phenomenon fully justifies the need for scientific research, more particularly so where juveniles are concerned.Among the girls comprized by the investigation, forty per cent, were under eighteen years of age, another forty per cent. — between nineteen and twenty-one years, and twenty per cent. — from twenty-two to twenty- -five years of age. During the investigation it appeared that the majority of the youngest girls (those under eighteen) could not be described as prostitutes in the strict sense of the term, in spite of their way of life and their behaviour which made them resemble prostitutes. The behaviour of such girls exhibited a number of symptoms of social deviation, in particular early begun and frequent sexual intercourse with various partners, strolling about at night time, spending time in the environment of social wrecks and outcasts, abusing of alcoholic drink, etc.The interviewing of eighty-two of the prostitutes was, as a rule, carried out at the police stations in various districts of Warsaw, and, moreover, later on also in the private homes of the investigators, at the domicile of the interviewed, etc. Part of the girls were interviewed in a women's jail.In every single case environment interviews have been carried out. They took place at the family homes of the girls, or in the homes of those persons with whom they were brought up. Moreover, interviews have been carried out in the schools which the girls under investigation had attended, as well as at the place of work, if they had worked prior to practicing prostitution. The data concerning the prostitutes’ judicial record (whether punished or not) have been scrupulously checked.It has been found possible to comprize a mere one-third of the girls under investigation in psychological and medical examination, mostly those who were serving a term of imprisonment in jail.One year after the termination of the research follow-up studies were carried out in every single case, and again, after nearly two years, they were once more repeated. The latest follow-up studies obtained come from the year 1960.The fundamental difficulties which have made it impossible to carry out deeper psychological and psychopathological investigation were connected, first and foremost, with the place where such investigation was conducted, and have been the reason why the material was elaborated mostly from a sociological angle. It would seem, however, that taking into account, first and foremost, the sociological aspect was fully justified (and has proved to be fruitful), since an investigation of prostitutes carried out almost exclusively from a psychiatric angle fails to explain properly the process of such persons going to wreck socially. The girls who practice prostitution could be classified into various categories of prostitutes. The classification of the girls investigated has been carried out in accordance with the terminology accepted in their environment and with a complex criterion imposed, as it were, by the girls themselves. Such elements as: clothing and outward appearance, the place of making contacts with men and of spending time with them, the method and forms of winning them over, and, finally, the amount of pay received are, in the opinion of the prostitutes themselves, a testimony of their belonging to such or such other circle.The two fundamental categories of persons who practice prostitution, singled out on the basis of the set of elements enumerated above are the so-called  “premises” and the “street” prostitutes. That division, however, is inadequate in a fundamental way, since it does not single out, from the total number of street prostitutes, that group of persons who, from the point of view of the general living standards of the women who practice prostitution, stand considerably lower than their remaining companions from the street. Because of the criterion accepted, therefore, the most adequate seems to be a threepartite division, comprizing the following categories: (“ A” ) premises prostitutes, (“ B” ) higher-class street prostitutes, and (“C” ) — lower-class street prostitutes.The above division of the persons investigated has greatly helped to notice the various aspects of the complicated problem of prostitution. In the course of the investigation it has appeared that the stereotyped notion of “ prostitute in general” ought to undergo revision. The differences which divide from each other the prostitutes of the several categories are so great, beginning with the origin of the process of their social derailment and ending with their present-day way of life, that it is really hardly possible to speak of the type of the average prostitute. It would seem that the above problem had so far been underestimated in the research on prostitution. The social environment, from which the girls under investigation hailed, was divided according to the following groups: working-class, peasant, lumpen-proletariat, educated and the so-called “ miscellaneous” . 51 per cent, of the girls come from working-class families (in the broad sense of the word), while only one-third of their parents were skilled workers, while another one-third were manual workers without any training, employed as porters, janitors, coachmen, cleaners, etc.A relatively small group of girls hailed from the country (18 per cent.). Their parents were agricultural labourers or small-holding peasants.The third group of girls were the daughters of representatives of the lumpen-proletariat (lowest, socially degraded stratum of the proletariat). 12 per cent, of the girls hailed from an environment of that type.The fourth group of the girls investigated hailed from environments described as “miscellaneous” . Here we have included those girls, whose parents worked at trades widely differing from one another (e. g. hairdresser and typist, waiter and factory girl, etc.), while the type of home environment itself did not present any close analogies with those previously enumerated. Altogether 14 per cent, of the population investigated belong to that group.The fifth type of environment distinguished by us in this material is the intelligentsia. 5 per cent, of the girls hailed from intelligentsia families. The data concerning the level of education of the parents of the prostitutes under investigation, and the economic situation of the family environment look as follows:In the working-class families the parents or guardians of more than one-half of the total number of the girls had barely gone through a few classes of the elementary school, or even are illiterate. The economic situation of the working-class families under investigation does not present any uniform picture: one-half of the families live in middling material conditions, another half — in bad ones.In the lumpen-proletariat families the level of the parents’ education presents a critical picture. Not a single one of all the parents has finished elementary school. They live mostly in distant suburbs, in one-room dwellings, under poor hygienic conditions. Their material situation is bad. In the peasant families, from which the girls under investigation hail, the level of the education of the parents is similarly low. The financial conditions of such families exhibit considerable divergencies, from bad ones in several families burdened with a great number of children, right up to a prosperity which enabled them to maintain and educate their children in town.The intelligentsia families from which some of the girls hail are characterized by a favourable financial and housing situation. The girls’ parents have a secondary, or even a higher, education.In the family environments described as “miscellaneous” considerable differences as to the education level of the parents make their appearance. The financial situation of such families is moderately good or good.From the above data it results that 72 per cent, of the total number of parents are people who either did not have even an elementary education, or else were altogether illiterate, and that one-half of the total number of the girls under investigation were brought up in at least middling financial conditions, and another half — in poor conditions. A characteristic feature, which makes its appearance with nearly all the categories of girls, is the m u l t i p l i c i t y o f e d u c a t i o n a l  e n v i r- o n m e n t s through which they went in the period of their childhood and early youth.The children who were brought up by one of the parents only, or else by a stepfather, stepmother or by strangers, changed their educational environment particularly frequently.Among the one hundred girls, who, it should be noted were selected at random for investigation, as many as forty-five were half-orphans, and fifteen — total orphans, while approximately thirty per cent, have live through a wrecking of their parents’ marriage. Altogether as many as eighty-four per cent, of the girls have been deprived of a normal, full family, while only fifteen per cent, of their number ceased to be under the guardianship of both parents at the age of from fourteen to eighteen years, and all the remaining ones — below the age of fourteen. Such facts to a large extent explain the changing destinies of the girls under investigation, as well as the multiplicity of the environments in which they were brought up (aproximately one-third of them spent at least a couple of years in State Homes for Children).Barely seventeen per cent, spent both their childhood and their youth in one single family home. The girls who had changed their ,,homes“ twice or three times account for forty-two per cent, of the total number, four or five times — for twenty-six per cent., from six to ten times — for fifteen per cent.The lack of a feeling of stability, the necessity of breaking emotional ties, changing authorities and requirements — all that exerted a powerful influence upon the mental development of those children. Being already adults they more than once expressed themselves on that subject with a grudge and a feeling of having been wronged.E d u c a t i o n a l c o n d i t i o n s assumed a most unfavorable outlook in the case of nearly the whole group of girls.One-third of the girls had made a direct experience of the consequences of living under the same roof with a habitual drunkard, while a total of two-thirds came into contact with various forms of intense alcoholism. Every fourth girl was brought up in a family where both parents or guardians abused of intoxicating drink.Other undesirable elements of the educational atmosphere, such as: frequent brawls and quarrels, a bad married life of the parents, their conjugal infidelity etc. made their appearance in the families of seventy per cent, of the girls under investigation.Bad relations between the children and their stepfather or stepmother appeared in nearly one-third of the families.A considerable group of the girls (approximately forty per cent.) had met, in the family home, with emotional coolness, indifference or hostility on the part of their stepmother, stepfather, father or mother.A lack of rational educational methods made their appearance with more than one-half of the family environments under investigation, while a general lack of guardianship and control over the children prevailed in three-fourths of the homes. In about one-half of such cases one could definitely speak of a convergence between the absorbing professional work of the mothers and the lack of care of the children (altogether seventy-two per cent, of the mothers worked for a living outside the family home). A total absence of any single of the above-mentioned negative educational factors appears in a mere one per cent, of the families investigated.It should be emphasized that it was merely in five per cent, of the families that th‘e mothers also practiced prostitution (or else the female guardians of the girls did), while with another five per cent, of the cases there subsisted a suspicion of the mothers practicing prostitution.It has not been found possible to collect any more precise information concerning the parents’ criminal record; there can be no doubt, however, that at least twenty per cent, of the fathers and mothers had been prosecuted before the law-courts for various offences. The data concerning the b r o t h e r s and s i s t e r s of the girls under investigation bear witness to the significant fact that, in two-thirds of the families, not only the prostitute investigated herself, but also at least one of her brothers or sisters betrayed certain symptoms of having gone to wreck socially. There were cases of hooliganism (twenty-five per cent.), of criminality (thirty-four per cent.), of far-gone alcoholism (twenty-two per cent.), of prostitution (seventeen per cent.). Moreover, several of the sisters of the girls under investigation led a sexual life fairly approximating prostitution (thirteen per cent). In a number of families such phenomena made their appearance concurrently.It has been found, moreover, that the process of social degradation of the girls’ brothers and sisters as a rule occurred in those cases, where there was a particular intensity of educationally undesirable elements in the family environment. An application of the X2 test has made it possible to demonstrate whether and if so, in what cases, there exist bases for rejecting the hypothesis of the independence of the variables which characterize the environment of the girls under investigation, of the category of prostitutes. Such hypotheses have been checked on a level of significance amounting to 0.05. As a standard of the degree of dependence, Tchuprov’s coefficient of contingency T, has been accepted.Below are some of the significant statistical dependences which have been brought to light.The “premises” prostitutes (“ A" ) differ from the prostitutes of the remaining categories by their social origin: they come from working-class or peasant environment considerably more rarely than do the remaining girls. Illiteracy among the parents of the “premises” prostitutes makes its appearance considerably more rarely then is the case with the families of the other girls. The financial and housing conditions in which the girls belonging to this group have been brought up were considerably better than in the case of the remaining persons. The “premises” prostitutes more rarely changed their educational environment, and remained for a longer time among their complete families. On the other hand, they came much more frequently than the remaining prostitutes into contact with such a destructive factor as a bad married life of the parents, and with that specific atmosphere of the family home, in the formation of which an essential role was played by the matrimonial infidelity of the parents.A peasant social origin distinguishes in a characteristic way the group of street prostitutes of the lower class (“C” ) out of all the other prostitutes. The percentage of illiterates among their Barents is the highest. The girls who had found their way into that circle of prostitutes had been brought up in financial conditions worse than those of the remaining persons. They were also deprived at an earlier date of guardianship of both parents. It is also in the group that the percentage of entire orphans is the highest.The higher-class street prostitutes (“B”) more frequently than the others girls investigated hailed from working-class families domiciled in Warsaw. As distinguished form the group “C” prostitutes, the majority of whom had spent their childhood in critical finacial conditions, as well as from the “premises” prostitutes, a large number of whom had a good situation in this respect, the ,,higher-class“ street prostitutes were brought up in average, middling material conditions. The data concerning the e d u c a t i o n o f t h e p r o s t i t u t e s under investigation present a picture fairly unfavourable for the total of the population investigated.Fifty-one per cent, of them have not completed their elementary education, while a mere three per cent, have a secondary education. As many as eighty-six per cent, of the girls have interrupted their training, either at the elementary, or at the secondary school.The girls who stayed on in the same form for a second or a third year broke away from school with particular ease. Fifty-five per cent, of the girls under investigation repeated one or several forms. That was mainly caused by two factors: considerable pedagogical neglect, the lack of any assistance or even control on the part of the girls’ parents, and the low level of intelligence with a great many of the investigated. The abandoning of school prior to finishing it was of the significant statistical dependences which have been moreover more than once caused by difficult general conditions  whether family of personal, in which many of the girls found themselves (deportarian to Germany during the war, the absolute necessity of taking care of younger brothers and sisters, etc.).In so far as the educational difficulties which the prostitutes under investigation caused in the period of their childhood are concerned, it must be stated that, out of the eighty-five girls about whom it has been possible to collect more detailed data, more than one-half (forty-five) were considered to be “ difficult” children. In the anamneses their own mothers describe some of them as being impatient, prone to outbursts of anger, aggressive, others again — as restless, of unequal disposition, excessively excitable, over-active, nervous, while others still were described as apathetic, lazy, passive, unwilling to undertake even the smallest effort.  Part of the girls under investigation can undoubtedly be classified as psychopaths, neurotics and persons with encephalopathy symptoms. Over and above this, seventeen per cent, of them were cases of mental deficiency (morons). Altogether, fifty-three per cent, of the prostitutes under investigation exhibited, in their childhood, obvious personality disorders and pathological traits.Concerning the girls who did not pass for particularly difficult at the time of their childhood and who did not distinguish themselves, in an unfavourable sense, against the background of their co-equals, brothers and sisters, many mothers yet asserted that they were characterized by frivolity, a lack of perseverance, as well as a considerable susceptibility to the influence of the environment. The question of whether, within this group of girls, persons with features of e. g. a psychopathy of the type of life instability were represented in any numerical strength or not, cannot be decided, because of the lack of adequately precise data.It should be remarked, moreover, that twenty-seven per cent, of the investigated, even though they did not exhibit features of mental deficiency yet were at an intelligence level below average. The initial symptoms of the process of social degradation made their appearance with twenty-one per cent, of the investigated — prior to their completing their thirteenth year of age, with thirty- height per cent. — between the fourteenth and fifteenth year of age, with forty-one per cent. — in their sixteenth year of age or later.Approximately three-fourths of the investigated ran away from home. Such flights were mainly caused by: fear of punishment, not feeling well at home, revolt because of having been placed, against their will, in an educational institution or with strange people, etc.Thefts, during that initial stage of demoralization, were committed by eighteen per cent, of the girls, whereas theft as a phenomenon isolated from other symptoms of the girl’s degradation rarely made its appearance (a mere eight per cent, of the cases), unless we also take into consideration sporadic petty thefts in the family home or at school, which were committed by twenty per cent, of the investigated.A characteristic feature is the participation of the girls under investigation in three types of groups of seriously demoralized young people: hooligan (thirty-one per cent, of the girls), hooligan-and-thieving (twelve per cent of the girls), and the so-called “ premises group” (twenty-five per cent, of the girls).The circles of young people who frequented a luna-park (entertainment park) or such similar place, in which many of the girls investigated spent their time, were easily transformed into groups of a more or less hooligan character. The presence, there, of individuals who had gone through a certain “ period of training” in a hooligan gang, and acquaintance with the “merits” of intoxicating drink particularly favoured such a change. Cases of coming forward, in an aggressive manner, against their environment, which at first has been sporadic, fairly rapidly became a habit and a permanent element in the life of the group. One of the principal attractions of the life within such a group was frequent sexual intercourse between boys and girls. The joining of hooligan-and-thieving groups by the girls frequently followed a course approximating that described above. Such groups, because of their very character, were, as a rule, better organized and more compact. Usually, they also had at their disposal their own accommodation — a “ dive” (thieves’ den).Part of the girls under investigation joined the life of groups of young people of yet another sort, namely so-called premises groups. The fact of frequently staying away from home in search of company and entertainment in cafés, dancing resorts, etc. was, in many instances, connected, in some manner or other, with the fact that the girls investigated did not feel well at home, in an atmosphere of family quarrels, of a very bad married life of the parents, of their conjugal unfaithfulness, etc. What has also contributed to their joining the circles of young people who spent their time in entertainment premises were, moreover, various other personal experiences of the investigated, and, among others, their first and unsatisfactory sexual experience, which brought about an early awakening of erotical desire and the search for ever new partners.Sexual promiscuity unconnected, in a special way, with the girl belonging to any comradeship group made its appearance in eighteen per cent, of the cases. It should be noted, however, that approximately one-half of those girls did not start their sexual experiences out of their own free will, but had been raped by adult men. All such girls began, after the above happening, to run away from home and to go in for an intense sex life. Out of the seventy-six g i r l s w h o h a d b e e n w o r k i n g for their livelihood prior to their beginning to practice prostitution, eighty-three per cent, had gone to work before the eighteenth year of their lives, including one-half who did so before they had completed sixteen years of age. The work which such girls had been able to get was, in an overwhelming majority of the cases, very poorly remunerated and mostly very unattractive, owing to the girls’ young age, their lack of education and qualifications.Sixty-one per cent, of their jobs was accounted for by manual work (factory worker, agricultural labourer, errand-girl, domestic servant, etc.), twenty per cent. — by half-manual jobs (shop assistant, conductress, waitress, etc.). The girls under investigation fairly frequently changed their place of work: on an average every one of them had worked 3.7 times. A factor which favoured that lack of stabilization in their trade was, first and foremost, the process of their social degradation, mostly already begun during that period, and, in particular, their connections with groups of seriously demoralized young people.A dishonest attitude to work, the missing of workdays, petty thefts at the place of work, etc. have caused twenty per cent, of the investigated to receive reprimands, while disciplinary action had been taken against as many as forty per cent., and another ten per cent, were prosecuted . before the law-courts by their place of work.It has been found possible to establish, by means of the x2 test, further differences between the several categories of the girls under investigation, other than those discussed previously (under item 7).The dependence between the level of education and the fact of the subsequent finding their way into the several categories of prostitutes has proved to be significant. The girls from the group of lower-class street prostitutes (“C”) have the poorest level of education, the ‘‘premises” prostitutes (“A” — the highest). Then, when checking in turn the hypotheses of a possible lack of dependence between the girls’ intellectual level and their belonging to this or that category, it was found possible to establish the following fact: persons intellectually below an average level could be met with, relatively most frequently, among the group (“C” ) prostitutes; relatively most rarely among those of group (“A”). The considerable pre-dominance of persons with an intellectual level below average (seventy-one per cent.) among the prostitutes of that lowest category, and of persons with a normal intellectual level among the “ premises” girls (seventy-seven per cent.) have caused the dependence between the variables enumerated to be particularly striking. This confirms the observation made in the course of the investigation, that the problem of a low intellectual level has played a role in the process of the degradation of but certain categories of prostitutes.The test of significance has, moreover, made probable the existence of a clear connection between the age of the investigated and the initial symptoms of the process of degradation, discussed previously, as well as between such symptoms and the fact of the girls belonging to the several categories of prostitutes. Thus e.g. flights from home and petty thefts, committed individually, most frequently made their appearance among very young girls (before their fourteenth year of age); participation in hooligan and hooligan-and-thieving groups has proved to be characteristic of those girls, who in time became street prostitutes, while participation in a group of young people frequenting some place of entertainment — of those girls, who were subsequently to become “ premises” prostitutes. The girls under investigation started their s e x u a l l i f e relatively early. Nearly one-half (forty-four per cent.) of them experienced their first sexual intercourse before they had completed their sixteenth year of age, and another group, equally numerous — between their seventeenth and their eighteenth years of age. Their first partner was mostly the boy with whom they “ went out” , or else a comrade from the group. Such first sexual experiences were, generally speaking, rapidly followed by others, with other partners.Questions which form part of the domain of sexuology were extremely difficult to establish under the conditions under which the investigation was carried out. It was barely in approximately one-half of the cases that it proved possible to obtain data concerning the sexual experiences of the girls under investigation, concerning the period when they were practising prostitution. The group of entirely frigid girls was represented by approximately thirty per cent, of the total number. Nearly one-half (forty-six per cent.) consisted of girls, who had average sexual experiences with those men, with whom they were emotionally bound, and, moreover, they occasionally experienced a satisfaction of their sexual drive even with chance “ customers” who appealed to them. The remaining girls (twenty-four per cent.) only achieved satisfaction in sexual intercourse, when their partner was a man for whom they had some feeling. The data concerning the beginnings of prostitution with the girls investigated looked as follows.Those girls who spent a lot of their time in groups of young people in cafés, places of entertainment, etc. generally speaking reached prostitution within a very short time. The influence of intoxicating drink, the example and persuasion of girl-friends already demoralized, numerous offers on the part of the men who spent a lot of their time in such places, and such-like factors created circumstances which favoured the taking up of the profession of prostitute. A most essential factor, moreover, consisted in the large sums of money frequently offered and given to the girls by men (such sums oftentimes amounted to the equivalent of one half of the girl’s monthly wages at her place of work).The girls who were members of hooligan groups, as a rule already seriously demoralized, not working, having no money of their own, usually easily found the way into a prostitutes’ environment, yielding to the example of girl-friends, who had been prostitutes previously. The girls who belonged to thieves’ groups began to practise prostitution in the hope of convenient and easy theft or else became prostitutes upon the demand of the group. Their appointed task was to provide convenient opportunities for the members of the gang to steal from their “customers”.  A certain part of the girls under investigation (fourteen per cent.) who did not have the support of a family home, taken from among those girls who had been prosecuted before the courts (principally ‘for theft) after completing their seventeenth year of age, found their way to a prostitutes’ environment only after having left prison, as a result of the example and persuasion of their fellow-prisoners.Thirteen per cent, of the girls began to practise prostitution because of having established contacts with either a procuress or a souteneur. The fact should be emphasized that, in the course of their practising prostitution, as many as approximately thirty per cent, of the girls investigated were bound up with souteneurs. The data concerning the under investigation, when c r i m i n a l i t y o f t h e p r o s t i t u t e s we take into consideration both the period preceding prostitution and the period of actually practising it, look as follows:Prior to their practising prostitution the criminality of the investigated was mostly limited to hooligan acts and to thefts. No criminal offences, not even any petty home or school thefts, were committed at that time by forty per cent, of the girls.During the period of their practising prostitution (the average duration of that period amounted to 5.4 years) as many as eighty-four per cent, of the investigated committed criminal offences. The latter were mainly offences against property and offences against the public peace (resistance to the police, brawls and scuffles when under the influence of drink, etc.). Offences against the public peace were committed by approximately sixty per cent, of the investigated.Offences against property (which as a rule consisted of thefts) were commiteed by seventy-six per cent, of the total number of girls investigated. The thefts mostly consisted in taking from a drunken “customer” his money or his watch. Thefts accompanied by the use of violence or robberies (eleven cases in all) were committed by the girls investigated always along with men, who organized such operations.Barely one-fifth of the girls never saw the inside of a prison. The rest served various terms of imprisonment and were detained under preventive arrest pending inquest mostly more often than once (most frequently from twice to five times).The majority of the criminal offences committed by the prostitutes investigated were connected with their practising their profession, and, first and foremost, with the environment in which such girls stayed and to which they accommodated themselves. Contrary to numerous opinions formerly expressed in the literature of the subject, we may now include thefts in the number of criminal offences more particularly bound up with prostitution. On the basis of the %2 test an obvious dependence has been found to exist between the“road” which had led them to prostitution, and the category of prostitutes.The higher-class street prostitutes (“B” ) significantly more often than the persons belonging to the other groups became prostitutes direct through their participation in hooligan-and-thieving groups.Among the lower-class street prostitutes (“C”) relatively the largest number began to practise prostitution after having come out of prison. That fact is closely connected with their homelessness, by which they significantly differ from the other girls investigated.The typical “road” of arriving at prostitution in the case of the premises girls was their previous participation in circles of young people who frequented places of entertainment. During the period when they practised prostitution the street girls committed offences against public peace considerably more frequently than did the premises girls.The test of significance has brought to light the fact, that there did not, however, exist any dependence between the lesser or greater intensity of offences against property and the fact of a girl belonging to this or that definite category of prostitutes. This is true, first and foremost, of theft, which has become one of the - elements of a prostitute's “profession”.  17 . The follow-up studies comprize the period of merely two years from the moment of the termination of research work, and this is precisely the reason why the data concerning the further destinies of the girls under investigation have, of necessity, but a limited scope.The age of the prostitutes under investigation at the time of the carrying out of such follow-up studies mostly amounted to from twenty-two to twenty-five years, and the average length of the period during which they had been practising prostitution — to 5.4 years.The breaks in the practising of prostitution, whether of longer or shorter duration, which took place in thirty per cent, of the cases, were principally brought about by the girl in question tying her life to some one man, who frequently was e.g. the girl’s previous “customer” . But unions of that type were not distinguished by their lasting character.Twenty-eight (i.e. thirty-four per cent.) of the prostitutes under investigation got married. The marriages of thirteen of their number took a favourable course: those women altogether broke away from their previous way of life. The marriages of ten of them have proved unsuccessful, and, after becoming separated from their husbands, those women once more began to practise prostitution. Five of the prostitutes have married thieves and souteneurs, and still continue to ply their trade.Out of the whole number of the remaining girls under investigation who were not married, a mere five have undertaken systematic work for a livelihood and have broken away from prostitution.Thus only twenty-two per cent, of the juvenile prostitutes investigated abandoned prostitution during either the period of the research, or else during that of the follow-up studies (together amounting to from four to five years).What is emphasized, first and foremost, in the c o n c l u s i o n of the contribution, is the fact that the process which leads a girl to prostitution is one of long duration.It grows out on the substratum of an abnormally functioning family and of personality disorders with such girls, whereas there exist, as early as during the period of their minority, clear and obvious harbingers of the beginning and increasing process of social degradation, in the form of a whole number of symptoms (such as e.g. their playing truant from school, running away from the family home, early begun and frequently repeated sexual intercourse with varying partners, spending time in the environment of socially degraded young people, the abusing of intoxicating drink, and the like).The laying hold, at an early date, of such and such like symptoms of general demoralization, and a proper interference at the suitable time could, in all probability, have prevented the later appearance of the phenomenon of prostitution among those girls.